Satisfaction of women with health service provider in outpatient department of Obstetrics and Gynecology at a Tertiary care hospital - Khatun, Ashia; Nahar, Khairun; Aktar, Mst Nurunnahar; Akter, Fatema Mahbooba; Rahman, Habibur (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Patient's satisfaction over the health care services is very important issue in Bangladesh. Objective: The purpose of present study was to find out the level of satisfaction of women attending in the OPD of Obstetrics and Gynecology department at a tertiary care hospital in Dhaka. Methodology: This descriptive type of cross sectional study was carried out in the OPD of Obstetrics and Gynecology department at Dhaka Medical College from September 2011 to October 2011 for a period of one month. All the women attending in Obstetrics and Gynecology department in outdoor service at Dhaka Medical College Hospital, Dhaka with the age group of 22 to 40 years were selected as study population. A purposive sampling method was used to collect the data. Results: A total number of 200 cases were taken for this study. Highly satisfied over the services delivered by the doctors was reported in 135 (65.8%) cases and service of nurses was satisfied 111(55.8%) of cases. Satisfactory waiting time (two hours) was 143(7l.9%) of cases and the satisfactory hospital environment was 127 (63.8%) of cases. Conclusion: In conclusion most of the women are satisfied to the treatment delivered by the doctors at the OPD of a tertiary care hospital. J Shaheed Suhrawardy Med Coll, 2014; 6(2):79-81